Short-Term Therapeutic Effects of Topical Corticosteroids on Refractory Dry Eye Disease: Clinical Usefulness of Matrix Metalloproteinase 9 Testing as a Response Prediction Marker - Ryu KJ (Dove Medical Press, 2021)
Kyung Jae Ryu,1 Seunghoon Kim,2 Mee Kum Kim,3 Hae Jung Paik,1 Dong Hyun Kim1 1Department of Ophthalmology, Gil Medical Center, Gachon University College of Medicine, Incheon, Korea; 2RudaCure Co., LTD, Incheon, Korea; 3Department of Ophthalmology, Seoul National University College of Medicine, Seoul, KoreaCorrespondence: Dong Hyun KimDepartment of Ophthalmology, Gachon University College of Medicine, Gil Medical Center, 1198, Guwol-dong, Namdong-Gu, Incheon, 21565, KoreaEmail amidfree@gmail.comPurpose: To compare the short-term therapeutic effects of topical corticosteroids in patients with refractory dry eye disease (DED) according to the tear matrix metalloproteinase 9 (MMP-9) point-of-care positivity.Methods: This study was conducted on 137 patients who were referred from other eye clinics, complaining of irresponsive DED or acute DED flares despite routine treatment with topical cyclosporin or diquafosol. The patients received treatment with topical corticosteroids for 1 month. DED was evaluated by SANDE (Symptom Assessment in Dry Eye) questionnaire, tear film breakup time, ocular surface staining score, and meibomian gland dysfunction stage. The InflammaDry MMP-9 immunoassay was conducted in more symptomatic eyes of all patients. The changes in the subjective symptoms were additionally surveyed as symptom improvement score.Results: The mean age of the patients was 57.8± 13.4 years, and the tear MMP-9 positivity was 73.0%. Topical corticosteroids treatment showed significant improvement of symptoms and signs in the patients with refractory DED irrespective of the positivity of MMP-9 (each p< 0.001). The changes in SANDE score and OSS, and symptom improvement score were higher in the MMP-9 positive group than in the MMP-9 negative group (p=0.002/0.010/0.011). The overall rates of subjective symptoms improvement and SANDE reduction were 73.0% and 90.6% after topical corticosteroids treatment, respectively.Conclusion: Short-term topical corticosteroids had excellent therapeutic effects in patients with refractory DED or acute DED flares, irrespective of the tear MMP-9 level. Tear MMP-9 positivity may serve as a reliable response predictor of topical corticosteroids treatment in DED.Keywords: dry eye disease, ocular surface inflammation, tear MMP-9 positivity, corticosteroid